PRAGMATIK DAN WACANA KORUPSI - BR Suryo Baskoro (Humaniora, 2014)
While semantics analyze the informative meaning, pragmatics focus its attention on the communicative meaning, which is what is implied (by the speaker/writer) in context. Therefore, discourses containing implicit elements, such as advertising discourse, political discourse, or humorous discourse, are resourceful and inspirational terrains for pragmatics-based studies. Perlocutionary act is one of the implicit elements as it implies the influencing power or effect on the the speaker’s/writer’s choices to the hearer/reader. This paper discusses the discourse of corruption, that is dominated by the informative meaning. Journalist’s choices such as menghukum ‘sentence’, divonis ‘be sentenced’, melakukan tindak korupsi ‘do corruption act’ are merely informative so that they have a low perlocutive power or low pragmatic power. Critical pragmatic analysis indicates that such choices do not show the journalist’s sidedness to the low class society that is most harmed by the corruption acts. The purpose of this paper is to encourage journalists to be more empathetic to the lower class society and to make choices which have a higher perlocutive power in order to bring harder effect to the targeted segment, corruptors.